2020
DOI: 10.1111/jog.14381
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women's preferences for prenatal genetic testing: A single‐center study in Japan

Abstract: Aim: To evaluate how many pregnant women would prefer to undergo prenatal genetic testing (GT) if they received adequate information during early gestation. Methods: We examined the preferences for prenatal GT among pregnant women visiting our general outpatient clinic before 16 weeks' gestation between September 2014 and September 2017. We provided them with informational brochures about prenatal GT at their first visit. Women always received genetic counseling (GC) before undergoing GT of their own choice. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This would be explained by higher awareness of congenital anomalies in pregnancy in women of advanced maternal age. 12 Multiparous women were less likely to take FA even having multiple chances in each pregnancy to learn about FA supplementation. A study demonstrated that awareness of the need for FA supplementation, together with preconceptional counseling and knowledge about NTDs, were strongly related to the intake of FA during the appropriate period.…”
Section: Resultsmentioning
confidence: 99%
“…This would be explained by higher awareness of congenital anomalies in pregnancy in women of advanced maternal age. 12 Multiparous women were less likely to take FA even having multiple chances in each pregnancy to learn about FA supplementation. A study demonstrated that awareness of the need for FA supplementation, together with preconceptional counseling and knowledge about NTDs, were strongly related to the intake of FA during the appropriate period.…”
Section: Resultsmentioning
confidence: 99%
“…However, this model can be time-intensive and is not practical for serving a large population [7]. Although the implementation rate of prenatal testing in Japan where prenatal screening policies have not been adopted was reported to be <10% [8,9], a recent study in Japan suggested that onethird of pregnant women would choose to undergo prenatal testing after being provided information on prenatal testing at their first prenatal visit [10].…”
Section: Introductionmentioning
confidence: 99%